BHOJANA PATIPATTI: APPLICATION OF BHOJANAMATTANNUTA IN THE TREATMENT OF DISEASE BASED ON THERAVADA BUDDHISM - Kanjanasiri, Chonticha; Vajirapañño, Phramaha Daosayam (Journal of Graduate MCU KhonKaen Campus, 2020)
The aim of this academic paper was to present the concept of two kinds of diseases in Buddhism i.e. body disease (Kayikaroka) and mental disease (Cetasikaroka). The whole body diseases have cause to disease from an element, Physical laws, year old , animal, method, food , mind and action (Kamma) including heart, hunger, thirst. There is no moderation in eating, to receive harm. The causes of mental disease were greed , hatred and delusion. Bhojanapatipatti: there are10 eating doctrines. It is also Buddha’s method to promote direct healthy man. This is because, if everyone follow the 10 eating doctrines moderately. The food eating not luxurious or enjoyment of these foods. It is called that Buddhist eating food doctrines are eating for benefits to health really.